2007
DOI: 10.1007/s00192-007-0493-7
|View full text |Cite
|
Sign up to set email alerts
|

Combined trans- and periurethral injections of bulking agents for the treatment of intrinsic sphincter deficiency

Abstract: The purpose of this study was to compare Contigen combined with Durasphere to Contigen injections alone for the treatment of stress urinary incontinence (SUI) with intrinsic sphincter deficiency (ISD). Subjective and objective incontinence outcomes were compared at 2 weeks and 6 months. We compared rates of urinary retention and future incontinence surgery between groups. Thirty-three women underwent combined injections, and 51 underwent Contigen injections. Two weeks postoperatively, more women in the combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…To date, there is no consensus in the literature on the best treatment to choose and various options may be considered, mainly represented by bulking agents, artificial urinary sphincters and slings [1–4]. The role of bulking agents, which is surely the least invasive technique with an acceptable short‐term cure rate (60–80%) [22,23], was revised recently, because of the dramatic decrease in continence rate during the mid‐term follow‐up (25–40%) [5,23]. Also, the use of artificial urinary sphincters in women has been limited and is usually reserved for those patients with ISD caused by multiple failed anti‐incontinence procedures or congenital abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no consensus in the literature on the best treatment to choose and various options may be considered, mainly represented by bulking agents, artificial urinary sphincters and slings [1–4]. The role of bulking agents, which is surely the least invasive technique with an acceptable short‐term cure rate (60–80%) [22,23], was revised recently, because of the dramatic decrease in continence rate during the mid‐term follow‐up (25–40%) [5,23]. Also, the use of artificial urinary sphincters in women has been limited and is usually reserved for those patients with ISD caused by multiple failed anti‐incontinence procedures or congenital abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Koduri et al [18] conducted a retrospective study, which established that prior anti-incontinence surgery was a factor showing a trend toward the long-term success of PCI. Sokol et al [19] compared collagen injection alone and collagen combined with Durasphere injection for the treatment of ISD cases. They found that combined injection did not improve the outcome over collagen injection alone.…”
Section: Collagen Injectionmentioning
confidence: 99%
“…Other options proposed for the treatment of this worse‐prognosis group of patients include mainly urethral bulking agents and artificial urinary sphincters (AUS). The role of bulking agents, which is surely the least invasive technique with an acceptable short‐term cure rate (60–80%), was revised recently, due to the dramatic decrease in continence rate during the mid‐term follow‐up (25–40%) . The diffusion of AUS has also been limited, despite a reported cure rate >85%, by the risk of device revision or explantation due to mechanical complications (13.6%) and the relevant costs .…”
Section: Introductionmentioning
confidence: 99%
“…The role of bulking agents, which is surely the least invasive technique with an acceptable short-term cure rate (60-80%), was revised recently, due to the dramatic decrease in continence rate during the mid-term follow-up (25-40%). [5][6][7] The diffusion of AUS has also been limited, despite a reported cure rate >85%, by the risk of device revision or explantation due to mechanical complications (13.6%) and the relevant costs. 8 In this scenario, the suburethral tension adjustable sling (Remeex system) was proposed as a new device which combined the advantages of a less invasive approach with the opportunity of sling re-adjustment in order to increase the success rate and overcome the complications generally reported after the positioning of other compressive pubovaginal slings.…”
Section: Introductionmentioning
confidence: 99%